2000
DOI: 10.1590/s0041-87812000000100002
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional follow-up of critically ill infants receiving short term parenteral nutrition

Abstract: SUMMARY: Few studies have tried to characterize the efficacy of parenteral support of critically ill infants during short period of intensive care. We studied seventeen infants during five days of total parenteral hyperalimentation. Subsequently, according to the clinical conditions, the patients received nutritional support by parenteral, enteral route or both up to the 10 th day. Evaluations were performed on the 1 st , 5 th , and 10 th days. These included: clinical data (food intake and anthropometric meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
3
7
0
4
Order By: Relevance
“…Merritt et al (1985) [38] suggested that hypoalbuminemia is associated with inflammation, as in pneumonia, rather than being a common marker of protein [22] or caloric deficiencies [39]. Our data on plasma albumin during the acute phase are comparable to those obtained by many authors [22,25,36,43] as they indicated a negative linear correlation between plasma albumin and the length of oxygen therapy in G1. Hypoalbuminemia during inflammation [44] and during the edematous phase of PEM (i.e., Kwashiorkor and marasmic Kwashiorkor) [45] is due to reduced synthesis.…”
Section: Albuminsupporting
confidence: 87%
See 2 more Smart Citations
“…Merritt et al (1985) [38] suggested that hypoalbuminemia is associated with inflammation, as in pneumonia, rather than being a common marker of protein [22] or caloric deficiencies [39]. Our data on plasma albumin during the acute phase are comparable to those obtained by many authors [22,25,36,43] as they indicated a negative linear correlation between plasma albumin and the length of oxygen therapy in G1. Hypoalbuminemia during inflammation [44] and during the edematous phase of PEM (i.e., Kwashiorkor and marasmic Kwashiorkor) [45] is due to reduced synthesis.…”
Section: Albuminsupporting
confidence: 87%
“…G2 patients exhibited a milder underweight status compared to G1. The observed low ZWA on admission agreed with the findings of others [22][23][24][25]. From a review of studies from developing countries, Victora et al [26] concluded that underweight infants have a higher risk of mortality, case fatality and morbidity from pneumonia or ALRI.…”
Section: Growth and Nutritional Statussupporting
confidence: 86%
See 1 more Smart Citation
“…Nitrojen dengesi, vücut proteinlerinin kaybı veya kazanılmasının bir göstergesi olabilir, ancak tek başına bir hedef değildir. Bu nedenle malnutrisyonda değişiklik gösteren dört plazma protein düzeyiyle ilgili olarak albüminin düşük, transferrinin orta derecede, prealbümin ve retinol bağlayıcı proteininse yüksek derecede duyarlı olduğu gösterilmiştir (24).Yoğun bakım ünitelerinde nutrisyon takibi yapılan malnutrisyonlu geriyatrik hastaların %42,9'u kombine enteral-parenteral, %3,1'i enteral, %18,5'i parenteral ve %7,6'sı oral yollarla beslenmiştir. Hastaların serum protein değerleri, hastanede kalış süresi ve mortalite açısından fark görülmemiş, ayrıca hastaneye yatış ve nutrisyonel destek sonrası biyokimyasal parametreler arasında herhangi bir farklılık saptanmadığı bildirilmiştir.…”
Section: Discussionunclassified
“…Estas mudanças levam a subnutrição energético-proteica caracterizada pela perda de proteína corpórea e do depósito de gordura (Thibault e Pichard, 2010;Prieto e Cid, 2011 internação hospitalar e duração da antibioticoterapia mais prolongada (Briassoulis et al, 2001;de Souza Menezes et al,2011;Tappenden et al, 2013). Estes eventos levam a um aumento na taxa de mortalidade, tornando prioritária a introdução precoce da terapia nutricional (Delgado et al, 2000(Delgado et al, e 2008Calder et al, 2010;Tappenden et al, 2013).…”
Section: Agradecimentosunclassified